FORMING A NEW ECOSYSTEM OF EDUCATION: FROM STOCK TO KNOWLEDGE FLOW - Sultanova Lola Sharafovna; Karimov Diyor Mukhtarovich (Journals Park Publishing, 2023)
The article considers the main trends in the formation of a new approach to education as a continuous process, where the stocks of fixed knowledge are much less important, in while diverse and interdisciplinary knowledge, in in particular participation in various information flows, everyone is getting more important and lead to the creation of new knowledge.
Keywords: education ecosystem, technology, globalization, social networks, heterodox learning providers, knowledge paradigms, fixed knowledge stocks, knowledge flows, social learning.